KAJIAN MACAM PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL 3 (TIGA) JENIS JAGUNG (ZEA MAYS L.) - Fitri Wahyuningsih; Sri Hardiatmi; Siswadi Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2020)
The research about “Study Kind of Animal Manures to Against Growth and Yield of 3 (Three) Types of Corn (Zea Mays L.)